Long‐term outcomes after endothoracic sympathetic block at the T4 ganglion for upper limb hyperhidrosis. Issue 11 (4th September 2013) - Panhofer, P.; Gleiss, A.; Eilenberg, W. H.; Jakesz, R.; Bischof, G.; Neumayer, C.
Abstract : Background: The aim of this study was to evaluate long‐term results, quality of life, satisfaction and compensatory sweating after endothoracic sympathetic block at T4 (ESB4). Methods: Patients who underwent an ESB4 procedure for palmar or palmoaxillary hyperhidrosis between 2001 and 2008 were included in a prospective study at a university hospital. Questionnaires devised by Keller and Milanez de Campos were applied to evaluate disease‐specific quality of life. Results: A total of 189 patients underwent 374 ESB4 procedures. Of 174 evaluated patients, 54 (31·0 per cent) had palmar and 120 (69·0 per cent) had palmoaxillary hyperhidrosis. Median follow‐up was 92 months. In both groups, treatment successfully reduced hyperhidrosis ( P < 0·001) and quality of life increased significantly after ESB4 ( P < 0·001), remaining stable after 5 years. Overall satisfaction rates decreased owing to the development of compensatory sweating and recurrence during follow‐up. Compensatory sweating affected 41 patients (23·6 per cent), and was severe in 11 (6·7 per cent) of 163 patients at 5‐year follow‐up; eight of these 11 patients had been treated for palmoaxillary sweating. The severity of compensatory sweating did not deteriorate with time. The severe recurrence rate increased to 11·0 per cent during follow‐up, and was twice as common in patients treated for palmoaxillary sweating as in those treated for palmar sweating (13·2 versus 6·1 per cent respectively). Nine reoperations (5·2 per cent) were performed for persistent sweating, recurrence or compensatory sweating. Conclusion: T4 endothoracic sympathetic clip application is safe and effective in patients with upper limb hyperhidrosis, with stable long‐term improvements in quality of life. Abstract : Durable improvement in quality of life